Analisis Capital Adequacy Ratio (CAR) Dan Non Performing Financing (NPF) Terhadap Profitabilitas Return On Assets (ROA) Pada PT Bank Syariah Indonesia Tbk Periode Tahun 2020-2024 - Muhamad Endai; Koes Indrakoesoema (PT. Intelek Cendikiawan Nusantara, 2026)
This study aims to analyze the development of Capital Adequacy Ratio (CAR), Non-Performing Financing (NPF), and Return on Assets (ROA) at PT Bank Syariah Indonesia Tbk during the 2020–2024 period and to compare the results with banking industry standards. This research applies a descriptive quantitative approach using secondary data obtained from audited annual financial statements officially published by the company. The data were analyzed using descriptive statistical analysis and trend analysis based on standards established by Otoritas Jasa Keuangan. The findings indicate that the CAR ratio ranged between 20%–22% throughout the observation period and consistently remained above the minimum standard of 12%, reflecting a very healthy capital condition. The NPF ratio showed a declining trend until 2023 and remained below the maximum threshold of 5%, indicating controlled financing quality. Meanwhile, the ROA ratio gradually increased from 0.92% in 2020 to 1.71% in 2024, and in the last two years it exceeded the 1.5% benchmark, demonstrating improvement in the bank’s ability to generate profits from its total assets. Overall, the development of these three financial ratios indicates that the bank maintained stable and sound financial performance during the 2020–2024 period based on capital adequacy, financing quality, and profitability indicators